Data mining for business analytics : concepts, techniques, and applications in R /: concepts, techniques, and applications in R. (2017) - Shmueli, Galit, 1971-; Bruce, Peter C, 1953-; Yahav, Inbal; Lichtendahl, Kenneth C, 1969-; Patel, Nitin R (Nitin Ratilal)
No abstract available